Pengaruh Gaya Kepemimpinan terhadap Prestasi Kerja Karyawan (Studi pada KPRI Bima Jaya Pasuruan) - Sasongko, Totok (Jurnal Aplikasi Manajemen, 2009)
Organization constitutes a place for the interaction of two persons or mire involving the relationship between leader and subordinate. An organization can be success or failed due to leadership. When the leader applies favorable leadership style, work enthusiasm increases and employee's work achievement improves. The objective of research seems: (1) to understand the simultaneous effect of task-oriented leadership style and relation-oriented leadership style on work achievement of the employees in KPRI Bima Jaya Pasuruan; (2) to observe the partial effect of task-oriented leadership style and relation-oriented leadership style on work achievement of the employees in the KPRI Bima Jaya Pasuruan. Type of research classifies into explanatory research. Research population includes the employees at KPRI Bima Jaya in the 2008. Sample counts to 54 respondents. Research instrument employs questionnaire. Analysis tool has been multiple regression using F-test and t-test. Results of research indicate that simultaneous and partial task-oriented leadership style and relation-oriented leadership style affect work achievement of the employees in the KPRI Bima Jaya Pasuruan, counting 28.0% (R-square).